Improving simulations of fine dust surface concentrations over the western United States by optimizing the particle size distribution. Issue 12 (17th June 2013) - Zhang, Li; Kok, Jasper F.; Henze, Daven K.; Li, Qinbin; Zhao, Chun
Abstract [1] To improve estimates of remote contributions of dust to fine particulate matter (PM2.5) in the western United States, new dust particle size distributions (PSDs) based upon scale‐invariant fragmentation theory (Kok_PSD) with constraints from in situ measurements (IMP_PSD) are implemented in a chemical transport model (GEOS‐Chem). Compared to initial simulations, this leads to reductions in the mass of emitted dust particles with radii <1.8 µm by 40%–60%. Consequently, the root‐mean‐square error in simulated fine dust concentrations compared to springtime surface observations in the western United States is reduced by 67%–81%. The ratio of simulated fine to coarse PM mass is also improved, which is not achievable by reductions in total dust emissions. The IMP_PSD best represents the PSD of dust transported from remote sources and reduces modeled PM2.5 concentrations up to 5 µg/m3 over the western United States, which is important when considering sources contributing to nonattainment of air quality standards.